KEBIJAKAN PEMERINTAH TENTANG PAJAK - Simatupang, Wilson; Jhon Kristopel Manalu; Remus Silalahi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Government policy is an important tool in regulating the life of the nation and state, including in the economic field. One policy that has a strategic role is taxation policy. Taxes are the main source of state revenue used to finance national development and public services. This study aims to analyze the role of government policy in the field of taxation and its impact on development and community welfare. The method used is a literature study by reviewing various sources of literature related to taxation policy. The results of the study show that effective tax policies can increase state revenue, encourage economic growth, and create social justice.